Colorectal cancer chemotherapy during COVID-19 pandemic - Sainath Bhethanabhotla; Raja Pramanik; Priyanka Srivastava; Prashant Mehta; Amol Patel; Bivas Biswas; Atul Batra; Vineet Govinda Gupta; Chandan Das; Shubh Mahindru (Indian Journal of Medical and Paediatric Oncology)
The management of patients with colorectal cancer during the current SARS-CoV2 pandemic opens a Pandora's Box. While the world is facing an unprecedented crisis of fighting a life-threatening infectious disease, patients with colorectal cancer are facing the dual challenge to fight cancer while protecting them from infection. We attempted to critically examine the existing evidence for chemotherapy in colorectal cancer in different stages of disease and suggest treatment options in these vulnerable patients. Treatment options which do not overburden existing health-care resources can be provided for patients with colorectal cancer patients requiring chemotherapy without significant compromise in efficacy or increase the risk of hospital acquired SAR-CoV-2 infection.